EPILEPTIC AND NON-EPILEPTIC PAROXYSMAL STATES IN CHILDREN. PRINCIPLES OF DIAGNOSIS AND THERAPY - L. M. Kuzenkova; V. M. Shaytor; O. V. Globa; R. F. Tepayev (Педиатрическая фармакология)
Convulsions, especially prolonged convulsion, are an urgent state associated with high risk of development of life-threatening complications and frequent development of metabolic disorders, multiple organ deficiency and acute brain damage. Paroxysmal states of both epileptic and non -epileptic nature and similar clinical presentation complicating diagnosis and selection of ethiopathogenetic therapy are among the most prevalent conditions in children. The article presents the issues of etiology, clinical presentation and differential diagnosis of convulsions in children. We formulated recommendations on care rendering in the event of development of epileptic and non-epileptic convulsions. The article also describes contemporary views on epileptic status as a life-threatening condition and principles of stepped therapy based on the duration of paroxysmal epileptic status.